Adesmia subtropicalis (Leguminosae, Papilionoideae, Dalbergieae), a new endangered species from the Brazilian Pampas - MONTEIRO, THIAGO COBRA E. [UNESP]; IGANCI, JOÃO RICARDO VIEIRA; MIOTTO, SILVIA T.S.; FORTUNA-PEREZ, ANA PAULA [UNESP] (Magnolia Press, 2021)
In the context of an ongoing taxonomic review of Adesmia subg. Adesmia ser. Bicolores, a new endangered species endemic to Rio Grande do Sul state, Brazil, is herein described. The new species present a long glandular ochraceous indumentum, flowers 10-15 mm long, and arilated seeds. Information about morphology, differences from closely related species, phenology, conservation status, and etymology are provided.
Keywords: Adesmia clade; Fabaceae; Pampa; Subtropical flora; Taxonomy